2018
DOI: 10.1111/ijfs.13957
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of emulsion gels formulated with sonicated soy protein isolate

Abstract: This study aimed to determine the effect of high‐intensity ultrasound (HIU) on physical properties of soy protein isolate dispersions (SPI) and their addition to emulsion gels (EG) containing soybean oil (SBO), inulin (IN) and carrageenan (CAR). Sonicated and non‐sonicated SPI dispersions were mixed with CAR, IN and SBO and heated at 90 °C for 30 min to gel the emulsion. An increase in solubility and oil binding capacity was observed in sonicated SPI dispersions (S‐SPI) compared to the non‐sonicated ones. HIU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The TR, WR, and FR were significantly decreased ( p < .05) with soy protein isolate increased. It is well known that as a binder or filling agent of commonly useful vegetable protein in the meat industry, soy protein isolate has a good water and fat holding capacity, excellent gelling and structuring behavior (Berghout, Boom, & Goot, ; Kang et al, ; Paglarini, Martini, & Pollonio, ). Meanwhile, the emulsifying activity of 11S globulins was much significantly improved at 200 MPa, which enhanced the emulsified stability of soy protein isolate (Tang & Ma, ).…”
Section: Resultsmentioning
confidence: 99%
“…The TR, WR, and FR were significantly decreased ( p < .05) with soy protein isolate increased. It is well known that as a binder or filling agent of commonly useful vegetable protein in the meat industry, soy protein isolate has a good water and fat holding capacity, excellent gelling and structuring behavior (Berghout, Boom, & Goot, ; Kang et al, ; Paglarini, Martini, & Pollonio, ). Meanwhile, the emulsifying activity of 11S globulins was much significantly improved at 200 MPa, which enhanced the emulsified stability of soy protein isolate (Tang & Ma, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound treatment caused cavitation bubbles collapse and increased local pressure and temperature in bubbles' surrounding area, resulting in unfolding of protein and breaking of peptide bonds, and exposing hydrophilic amino acid residues to water, thus improving the solubility of SPI. On the other hand, Paglarini and et al () found that the ultrasound treatment can reduce the SPI particle size, causing conformational changes in proteins and the formation of soluble protein aggregates, which can enhance protein–water interactions, resulting in higher solubility of SPI. The solubility of TSPI samples decreased drastically (Table ), which could be due to the formation of insoluble aggregates during cross‐linking (Song & Zhao, ).…”
Section: Resultsmentioning
confidence: 99%
“…Hu, Li‐Chan, Wan, Tian, and Pan () explored a novel approach to make SPI gel with higher gel strength by ultrasonication. Paglarini, Martini, and Pollonio () showed that high‐intensity ultrasound is an efficient tool to improve the functional properties of SPI dispersions increasing their solubility and oil binding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional emulsifying procedure, Kobayashi prepared monodispersed stable emulsion by using microchannel emulsification [33]. More researchers [34][35][36][37] used ultrasonic treatment to obtain small droplet size emulsion by benefiting from ultrasonic cavitation function [38]. It was reported that ultrasonic treatment can improve surface hydrophobicity, surface activity and protein aggregation.…”
Section: Introductionmentioning
confidence: 99%